Fully Buried Pipeline Floatation in Poro-Elastoplastic Seabed under Combined Wave and Current Loadings - Jian Leng; Libin Liu; Chencong Liao; Guanlin Ye (Journal of Marine Science and Engineering, 2024)
The floatation capacity of seabed pipelines has long been considered a key risk element during design, especially with the combined loading of waves and currents. This paper presents a two-dimensional coupled approach with a poro-elastoplastic theory to study the floatation of pipelines with the combined loading of waves and currents. The findings suggest that the proposed method is able to capture the mechanical performance of pipeline floatation. Pipeline floatation occurs in two distinct phases. In the initial phases, the pipelines float slowly with the cyclic loadings. In the second stage, when the backfill soil in the middle position of the pipelines begins to liquefy, the floating displacement increases obviously. The boundary constraints provided by the pipelines strengthen the backfill soil as well as accelerate the release of excessive pore water pressure. Meanwhile, a nonliquefiable region is formed under the pipelines. The floating displacement of the pipelines increases as well as current velocity, wave height, and wave period, and reduces with increased backfill soil permeability. Increasing the permeability coefficient of backfill soil can obviously restrain the floatation of pipelines.